STK11 and KEAP1 mutations in non-small cell lung cancer patients: Descriptive analysis and prognostic value among Hispanics (STRIKE registry-CLICaP) - Cordeiro de Lima, VC (2022)
Background: Mutations in STK11 (STK11Mut) and, frequently co-occurring, KEAP1 mutations (KEAP1Mut) are associated with poor survival in metastatic Non-small Cell Lung Cancer (mNSCLC) patients treated with immunotherapy. However, there are limited data regarding the prognostic or predictive significance of these genomic alterations among Hispanics. Methods: This retrospective study analyzed a cohort of Hispanic patients (N = 103) diagnosed with mNSCLC from the US and seven Latin American countries (LATAM) treated with immune checkpoint inhibitors (ICI) alone or in combination as first-line (Cohort A). All cases were treated in routine care between January 2016 and December 2021. The main objectives were to determine the association of mutations in STK11 or KEAP1 in these patients’ tumors with overall (OS) and progression-free survival (PFS), presence of KRAS mutations, tumor mutational burden (TMB), and other relevant clinical variables. To compare outcomes with a STK11Wt/KEAP1Wt population, historical data from a cohort of Hispanic patients (N = 101) treated with first-line ICI was used, matching both groups by country of origin, gender, and Programed Death-ligand 1 (PD-L1) expression level (Cohort B). Results: Most tumors had mutations only in STK11 or KEAP1 (45.6%) without KRAS co-mutation or any other genomic alteration. Besides, 35%, 8.7%, 6.8%, and 3.9% were KRASMut + STK11Mut, KRASMut + STK11Mut + KEAP1Mut, STK11Mut + KEAP1Mut, and KRASMut + KEAP1Mut, respectively. Based on KRAS status, STK11 alterations were associated with significantly lower PD-L1 expression among those with KRASWt (p = 0.023), whereas KEAP1 mutations were predominantly associated with lower PD-L1 expression among KRASMut cases (p = 0.047). Tumors with KRASMut + KEAP1Mut had significantly higher median TMB when compared to other tumors (p = 0.040). For Cohort A, median PFS was 4.9 months (95%CI 4.3–5.4), slightly longer in those with KEAP1mut 6.1 months versus STK11Mut 4.7 months (p = 0.38). In the same cohort, PD-L1 expression and TMB did not influence PFS. OS was significantly longer among patients with tumors with PD-L1 ≥ 50% (30.9 months), and different from those with PD-L1 1–49% (22.0 months), and PD-L1 < 1% (12.0 months) (p = 0.0001). When we compared the cohorts A and B, OS was significantly shorter for patients carrying STK1 [STK11Mut 14.2 months versus STK11Wt 27.0 months (p = 0.0001)] or KEAP1 [KEAP1Mut 12.0 months versus KEAP1Wt 24.4 months (p = 0.005)] mutations. PD-L1 expression significantly affected OS independently of the presence of mutations in STK11, KEAP1, or KRAS. TMB-H favored better OS. Conclusions: This is the first large Hispanic cohort to study the impact of STK11 and KEAP1 mutations in NSCLC patient treated with ICI. Our data suggest that mutations in the above-mentioned genes are associated with PD-L1 expression levels and poor OS.